The Effect of Workload and Compensation on Nurses Job Satisfaction at RSUD Dr. Moh Saleh Probolinggo City - Khotimah, Annisa Aprilia Husnul; Rini, Hesty Prima (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to determine the relationship between workload and compensation on job satisfaction among non-ASN nurses at Dr. RSUD. Moh Saleh Probolinggo City. This research used a questionnaire method to collect data from a population that included all 68 non-ASN nurses, with a sample size of 68 respondents obtained using a saturated sampling technique. The data analysis method used was the Partial Least Square (PLS) method. The research results show that workload contributes to nurse job satisfaction. Furthermore, compensation can also contribute to nurse job satisfaction. These findings look at the relationship between workload and compensation on job satisfaction of nurses at RSUD dr. Moh Saleh Probolinggo City.